DISCOURSE ANALYSIS OF QUESTIONS IN TEACHERS’ TALK - Hanifa Ratna Dewi; Lia Novita; Wahid Hasim (Institut Pendidikan Indonesia Garut, 2019)
The research entitled “Discourse Analysis of Questions in Teachers’ Talk”. This research was focused on investigating the type of questions and the purpose underlying the questions used by the teacher. The research used a qualitative descriptive study by observing classroom interaction specifically in teacher’s questions. The participants in this research were three English teachers from different vocational schools in Garut. The findings showed that the teacher applied various types of questions during teaching and learning with the most frequent use of convergent type of questions. It also was revealed that mostly the purpose underlying the teacher’s questioning was to encourage students’ thinking and focus on the content of the lesson. By the frequent number of convergent questions dominating during teaching and learning, it can be concluded that characteristics of teachers are the same. They still use typically a lower-level type of question. It was then suggested that teacher purposely plans and promotes a higher-level type of question for future classrooms.